Investigating The Rigid and Derivative Names in Kadi Burhaneddin Collection - ABDULLAH, Ibtisam Oraibi (Al-Adab Journal, 2021)
The origin of the common Turkish language which is known today as ''Ottoman Turkish Language'' comes from the era of Ottoman State and was wirtten in Arabic letters. It contains numerous Arabic, French, and English loanwords. And different social, political, economic and cultural Turkish phrases and expressions are obviously affected by the Arabic language.The paper aims at investigating the employed Arabic words in the collection of Kadi Burhanettin and clarifying its segments and morphological functions and studying the Turkish suffixes and auxiliary verbs which are used with Arabic words in addition to analyzing the using of the Arabic letters in old ottoman texts and their equivalents in modern Turkish language.